Twentieth-century Italian poetry : an anthology - Picchione, John, 1949-; Smith, Lawrence R. (Lawrence Richard), 1945 January 1- (Italian linguistics and language pedagogy series., 1993)
Twentieth-century Italian poetry is one of the most vital, innovative and influential bodies of literature on the European continent. This volume presents a selection of poems in the original Italian, with introductory material and notes in English.